1998
DOI: 10.1515/znc-1998-9-1021
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Modulation of the Ouabain-Sensitive (Na++K+)ATPase from Malpighian Tubules of Rhodnius prolixus

Abstract: The presence and regulation by hyperosmotic medium of the ouabain-sensitive (Na++K+)ATPase of the Malpighian tubule cells of Rhodnius prolixus was investigated. The ouabain-sensitive (Na++K+)ATPase activity was 5.4 ± 0.5 nmol Pi x m g-1 x m in-1. Vanadate 100 piM completely abolished this ATPase activity. In hyperosmotic medium, obtained by addi tion of 180 mM mannitol, the (Na++K+)ATPase activity was inhibited by 60%. When the cell lysates were preincubated in hyperosmotic medium for 30 minutes and the ATPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 2 publications
5
11
0
Order By: Relevance
“…Downregulation of Na + /K + -ATPase activity, for example, will enhance elimination of Na + . It is worth noting that regulation of the activity of the Na + /K + -ATPase by protein kinase C has been reported in Malpighian tubule cells of R. prolixus (Caruso-Neves et al, 1998).…”
Section: The Effect Of Ba 2+ On Vbl: a Role For Basolateral CL -Channelsmentioning
confidence: 95%
“…Downregulation of Na + /K + -ATPase activity, for example, will enhance elimination of Na + . It is worth noting that regulation of the activity of the Na + /K + -ATPase by protein kinase C has been reported in Malpighian tubule cells of R. prolixus (Caruso-Neves et al, 1998).…”
Section: The Effect Of Ba 2+ On Vbl: a Role For Basolateral CL -Channelsmentioning
confidence: 95%
“…Since different agonists and antagonist of purinergic receptors were used, it is less probable that the effect of adenosine on the (Na (Arenstein et al, 1995;Caruso-Neves et al, 1998). On the other hand, Maddrell and Overton (1988) (Riegel et al, 1998).…”
Section: Adenosine Subtype Receptormentioning
confidence: 99%
“…The addition of ouabain 1 mM did not change the RVI. Latter, we observed that hyperosmotic shock inhibited the (Na + +K + )ATPase activity but did not change the Na + -ATPase activity (Caruso-Neves et al 1998a, Figure 2). So it is possible to postulate that cell volume regulation during hyperosmotic shock involves the inhibition of the (Na + + K + )ATPase activity.…”
Section: Stress Conditionsmentioning
confidence: 83%
“…The presence of (Na + +K + )ATPase in the Malpighian tubule was confirmed by Lebovitz et al (1989) who cloned its α-subunit cDNA in the basolateral membrane of Malpighian tubule of Drosophila melanogaster. More recently, it was shown that a ouabainsensitive (Na + + K + )ATPase activity is present in the Malpighian tubule cells of Rhodnius prolixus (Grieco & Lopes 1997, Caruso-Neves et al 1998a.…”
Section: Sodium Pumpsmentioning
confidence: 99%